Active position of the country in the world market of agrarian products as an indicator of the underdevelopment level of its economy - Hanna Fedosieieva (Academicus, 2018)
The article examines the role of countries in the development of the world market of agrarian products. At the same time, the world production and exports of agrarian products are considered not only in terms of countries, but also in terms of the most consumed species. The main tendencies of international trade of agrarian products are described. At the same time, we discuss only those agrarian products which are raw materials or have undergone the primary processing. The author of the research wants to confirm or refute the existing opinion that the active position of the country in the world agrarian market is a kind of evidence of the underdevelopment level of its economy.